The Rationality Prohibition of Riba (Usury) - Sofhian Sofhian (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
Usury (henceforth called as riba) in fact has long been known and have been progressing in meaning. The study of riba was not only discussed seriously by Muslims but also other religions. If flashed back to more than two thousand years ago, the study of riba has been discussed by non-Muslims, such as Hindu, Buddhist, Jewish, Greek, Roman and Christian. In Islam, debate about riba and bank interest indicated that the problem of riba very closely related to the issue of muamalah especially those that occur in Banks and Non- Bank financial. Riba evolution concept toward interest cannot be separated from the development of the financial institutions. Therefore, this journal examine and analyze the substance of the issues of interest in a rational perspective, and at the end of this journal offers loss and profit sharing system as an alternative solution to the system of interest in transaction systems of bank and non- bank.